Insights into the role of aromatic cationic surfactants in tailoring interfacial polymerization for high-performance reverse osmosis membranes - Jie Gao; Yongkai Xu; Nanxiang Wang; Dingxian Jia; Mingjie Wei; Shuang Hao; Yunxia Hu (Advanced Membranes, 2025)
Surfactant-mediated interfacial polymerization (IP) has been recognized as a promising strategy for accurately modulation of the structure and performance of polyamide (PA) reverse osmosis (RO) membranes. While aromatic cationic surfactants have demonstrated potential in regulating IP processes, the influence of their molecular structure on IP process and their incorporation integrated into the PA layer remain unexplored. This work systematically investigates two model surfactants—benzalkonium chloride (BAC, single benzene) versus benzethonium chloride (BEC, dual benzene)—as molecular regulators during PA layer formation. The results reveal that both aromatic cationic surfactants facilitate the diffusion of m-phenylenediamine (MPD) from the aqueous to the organic phase, enhancing PA cross-linking, while simultaneously embedding into the PA matrix to modulate surface properties. Notably, BEC, due to its distinctive dual-benzene-ring structure, exhibits a superior ability to accelerate MPD diffusion, triggering more pronounced Marangoni convection during IP, which contributes to a higher leaf-like structure area (0.017 ​μm2) of the resulting PA layer. Additionally, the strong π–π interaction between BEC and the PA network leads to a high embedding ratio of BEC within the membrane. Consequently, the BEC-regulated RO membranes demonstrate enhanced perm-selectivity, alongside improved antifouling and antibacterial properties. This study presents novel perspectives on the strategic design of cost-effective and high-performance fabrication methods for RO membranes, demonstrating substantial promise for industrial applications.